Front-Loaded or Back-Loaded Fiscal Adjustments : What Works in Emerging Market Economies? - Clements, Benedict (IMF Working Papers; Working Paper ;, 2004)
This paper investigates the political and economic determinants of successful fiscal adjustment in 25 emerging market economies from 1980 to 2001. The results show that large and back-loaded fiscal adjustments have the highest likelihood of success. Fiscal consolidations based on expenditure cuts increase the probability of approaching and achieving fiscal sustainability but are insufficient to maintain it unless accompanied by revenue reforms. Adjustment episodes launched in countries where governments enjoy a parliamentary majority and do not face imminent elections, are found to be more successful. Fiscal consolidations undertaken under IMF-supported programs also have a higher probability of success.